Performance of UASB reactor treating waste activated sludge: Effect of electro-chemical disintegration on the anaerobic microbial population structure and abundance. (October 2022) - Feki, Emna; Karray, Fatma; Mhiri, Najla; Battimelli, Audrey; Sayadi, Sami; Khoufi, Sonia
Abstract: The electro-Fenton (EF) disintegration using iron electrodes was performed for the pretreatment of waste activated sludge (WAS). The effect of this electro-chemical pretreatment on anaerobic digestion (AD) performance and microbial population structure was studied. An improvement of biodegradability and bioaccessibility of organic matter was demonstrated. AD of pretreated WAS in an up-flow anaerobic sludge blanket reactor (UASB) resulted to an increase of biogas production by 60 % compared to control reactor without disintegration. PCR-DGGE and real-time qPCR analyses showed that the high abundance of bacteria and the coexistence of Coprothermobacter in the UASB digestate fed with disintegrated sample established a stable bacterial association which is in line with the AD performance. Besides, the increased number of methanogens along the process allowed the improvement of methane production in comparison to control reactor. Highlights: The effect of electro-oxidation on the enhancement of anaerobic digestion of activated sludge was examined. The electro-oxidation improved the physico-chemical quality of sludge for postbiological treatment. Semi-continuous anaerobic digestion of pretreated sludge demonstrated the enhancement of bioprocess. High biogas yield of 0.80 L/g VS was achieved by integration of electro-oxidation to anaerobic system. PCR-DGGE analysis revealed the change of bacterial community structure by electrooxidation integration.